Reforming the Legal and Institutional Framework for the Enforcement of Civil and Commercial Claims in Portugal - Pompe, Sebastiaan; Bergthaler, Wolfgang (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses the recent major reforms in the area of civil and commercial claims enforcement undertaken by the Portuguese authorities in the context of the IMF/EU-supported adjustment program. The economic literature has long recognized that slow claims enforcement affects economic growth, foreign direct investment, credit and labor markets, and firm size. The Portuguese authorities together with IMF/EU staff deployed a novel approach that has focused on incentives tackling weaknesses in the enforcement process with the aim of increasing the efficiency and effectiveness of claims enforcement and resolving court backlogs. The paper finds impressive quantifiable changes affecting, in particular, court backlog reduction, court processing speed, and private debt recovery. The economic literature suggests that this will impact positively on the payment culture and overall growth, even if such impact cannot be determined at this stage.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet